Answer:
y = 1/3x + 26/3
Explanation:
Original equation: y = -3x + 2
Perpendicular lines have the "opposite reciprocal" slopes of each other, meaning you flip the numbers and reverse the sign.
Slope of original equation: -3
Slope of perpendicular line: 1/3
How: Reciprocal, flip the numbers: -3/1 to -1/3, then reverse sign -1/3 to 1/3
Then you substitute (-2, 8) into the new equation: y = 1/3x + b
*there's b because you don't know the y-intercept yet
Substitute: 8 = 1/3(-2) + b
8 = -2/3 + b
Add 2/3 on both sides
b = 24/3 + 2/3
b = 26/3
*this is the y-intercept
Therefore, the perpendicular equation is: y = 1/3x + 26/3